¿Integración de migrantes vs. vínculos transnacionales? El papel del Estado emisor - Délano, Alexandra (Revista Mexicana de Política Exterior, 2022)
According to Alexandra Délano, recent research into migration has shown that maintaining ties with the country of origin and integration with the country of destination are not mutually exclusive processes. Ties with the motherland tend to grow weaker over time, with immigrants generally becoming fully integrated by the third generation, but often it is the government of the country of origin that encourages their continued existence. Critics argue that encouraging the upkeep of such transnational ties hinders integration. In the specific case of Mexico, the author illustrates that policies designed to reach out to migrants have both explicit and implicit objectives, including the furthering the government’s political and economic interests, the need to maintain its legitimacy in the domestic and international arena, and secure a continued flow of remittances. However, since the 1990s, programs targeting Mexican migrants in the United States have also aimed to improve their quality of life. In this context, the question core to this essay and that needs to be discussed at greater length is whether or not the services and programs Mexico provides via its 50 consulates and the Institute for Mexicans Abroad (IME) facilitate or hinder the integration of migrants into U.S. society. Délano attempts to gauge the impact of these services —which include preventive healthcare and medical references, adult learning and leadership programs, to cite just a few— on integration based on interviews with Mexican migrants resident in the United States, program coordinators and civil servants in six U.S. cities. He also looks at how the United States has reacted to Mexico’s activism on these issues and the implications of these programs within the broader debate on shared responsibility in the handling of migratory issues